Management of Oral Surgery in Patients by Anticoagulant Therapy - Ammad Jawed, Talha Tanveer, Imran Khan, Bilal Yousaf, Waqar Ali, Ammar Ali Khalid (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Oral surgery is a common procedure performed on patients for various reasons such as implant placement, tooth extraction, and other surgical interventions. Anticoagulant therapy is prescribed to patients to prevent blood clot formation, which can lead to serious conditions. Post-operative management of patients on anticoagulant therapy is also critical to minimize bleeding complications. Study design: It is a systematic and controlled based study conducted at Azra Naheed Dental College/ Superior University, Lahore and DOW International Dental College, Karachi for the duration of six months from July 2022 to December 2022. Material and Methods: The participants were divided into two groups. Group A (n=35) included patients treated with direct oral anticoagulants (DOACs) after oral surgery and group B (n=20) had patients treated with vitamin K antagonists. The average age of patients in DOACs and VKA group was 71.3±2.33 and 72.1±1.6 years respectively. Results: Stroke, atrial fibrillation venous thromboembolism and acute coronary syndrome was found in 4,5,24 and 2 patients respectively. In case of VKA group there were 2,3,14 and 1 patient hat suffered from stroke, atrial fibrillation venous thromboembolism, and acute coronary syndrome in the VKA group. The duration of surgery in DOACs and VKA group was 34.5±2.33 and 31.8±3.2 respectively. Conclusion: This study concludes that bleeding risk in patients having some dental surgeries can effectively be controlled by interrupting the DOACs therapy and then restarting it after surgery along with some local hemostatic agents. However, the efficiency of VKAs and DOACs will be the same when DOAC therapy will not be interrupted right before an invasive surgical procedure in case of patients having higher bleeding risk treatment. Keywords: Oral surgery, anticoagulant therapy and thromboembolic events.